Use of histamine‐2 receptor antagonists and risk of inflammatory bowel diseases: A systematic review and meta‐analysis of observational studies. (10th April 2022) - D'sa, Freya Felicia; Fernandes, Elaine Zourra; Kesarkar, Srushti Vaibhav; Swaminathan, Lavanya; Kunhikatta, Vijayanarayana; Rashid, Muhammed; Thunga, Girish; Chandran, Viji Pulikkel; Nair, Sreedharan
Abstract: What is known and Objective: The effect of histamine‐2 receptor antagonists (H2RAs) use causing inflammatory bowel diseases (IBD) has been reported in few isolated observational studies; however, pooled estimation of IBD risk has not been done. The present study was conducted to estimate the risk of IBD [Crohn's disease (CD), ulcerative colitis (UC) and microscopic colitis (MC)], among H2RAs users. Methods: Databases such as MEDLINE/PubMed, Scopus and Cochrane Library were searched from inception to January 2021. A bibliographic search of selected articles, random search in Google Scholar and ResearchGate were also performed for any additional studies. The observational studies which assessed the incidence or risk of IBD in H2RA users published in the English language were considered. Modified Downs and Black Checklist was used for quality assessment. Two independent reviewers were involved in study selection, data extraction and quality assessment; any discrepancies were settled through consensus or by consulting a third reviewer. Results: Four studies out of 2, 658 articles were included for this meta‐analysis. The meta‐analysis of 4 studies with 8939 participants revealed a significantly higher risk of IBD (OR: 2.27; 95% CI: 1.70–3.02; p < 0.0001) in H2RA users compared to non‐users. Similar significant relationships were observed in the subgroup analysis of adults ( p < 0.0001) and paediatrics ( p = 0.04). The quality of included studies was observed to be fair to good. What is new and Conclusion: Our findings indicate a significantly higher IBD risk among those who used H2RA compared to non‐users both in adults and in paediatrics. Further observational studies involving large populations are required to strengthen these results and to generalize these findings. Abstract : There is a surge in H2RAs use for managing gastric disease conditions. However, only few epidemiological studies have observed increased incidence of IBD among H2RA users, and the risk is not wellestimated. To estimate the risk of IBD following H2RA use, 4 observational studies were obtained from various databases using pre‐determined inclusion–exclusion criteria. The meta‐analysis of these studies revealed a significantly higher risk of IBD (OR: 2.27; 95% CI: 1.70–3.02; p < 0.0001) in H2RA users compared to non‐users, and similar significant results were observed in the subgroup analysis [Adults ( p < 0.0001) & Paediatrics ( p = 0.04)].